Inhibition of photoreceptor apoptosis in mice with retinitis pigmentosa through NF-κB/NLRP3 pathway suppression with Lycium barbarum polysaccharide - Ying Wang; Ying Deng; Jing Lu; Jun Peng; Yasha Zhou; Yijing Yang; Qinghua Peng (KeAi Communications Co., Ltd., 2023)
Objective: To explore whether Lycium barbarum polysaccharide (LBP) can reduce the apoptosis of retinal photoreceptor cells in retinitis pigmentosa (RP) mice by inhibiting nuclear factor-kappa B (NF-κB)/NOD-like receptor thermal protein domain-associated protein 3 (NLRP3) signaling pathway. Methods: (i) In vitro experiments, mouse retinal ganglion cells (661W cells) were divided into normal, model, LBP low-dose (LBP-L, 40 mg/L), LBP middle-dose (LBP-M, 80 mg/L), LBP high-dose (LBP-H, 160 mg/L), and positive drug control (NLRP3 inhibitor, 160 mg/L) groups. And the 661W cells were exposed to varying concentrations of H2O2 ranging from 50 to 400 μmol/L to determine the optimal concentration for inducing apoptosis (200 μmol/L). Then the cell viability was assessed using Cell Counting Kit-8 (CCK-8), while the apoptosis rate was detected by flow cytometry; the expression of NLRP3 was detected by immunofluorescence; and the expression of apoptosis markers was detected by enzyme-linked immunosorbent assay (ELISA) and Western blot (WB). (ii) In vivo assays were carried out with the use of C57/BL6 and Rd10 mice. The animal experimental groups were divided into normal, model, LBP-L, LBP-M, LBP-H, and NLRP3 inhibitor groups, in which the normal group was C57/BL6 mice and the other groups were Rd10 mice. Ten mice were included in each group, and the corresponding drugs were administered intragastrically for a duration of four weeks. NF-κB/NLRP3 pathway and the expression of apoptosis markers were observed by electroretinogram, histopathological examination, and WB to assess the effects of LBP on retinal photoreceptor cell apoptosis. Results: (i) In vitro experiments, compared with the normal group, the apoptosis rate of 661W cells in model group was significantly increased (P < 0.01), and the expression levels of key proteins of NF-κB/NLRP pathway, such as NLRP3, NF-κB, p-NF-κB, and pro-apoptotic protein caspase-3, were up-regulated (P < 0.01). The rate of Bax/Bcl-2 was increased (P < 0.01), and the concentrations of interleukin (IL)-1β and tumor necrosis factor (TNF)-α were significantly increased (P < 0.01). Compared with the model group, high dose of LBP decreased the apoptosis rate of 661W cells (P < 0.01), and down-regulated the expression levels of the key proteins of NF-κB/NLRP3 pathway, including NF-κB, NLRP3, p-NF-κB, and caspase-3 (P < 0.01). The rate of Bax/Bcl-2 was decreased (P < 0.01), and the concentrations of IL-1β and TNF-α were decreased (P < 0.01). (ii) In vivo experiments, high dose of LBP significantly increased morphological changes in the outer nuclear layer (ONL) thickness of Rd10 mice, as well as functional changes in the amplitudes of the a-wave and b-wave (P < 0.01), which also down-regulated the expression levels of NF-κB (P < 0.05), NLRP3, p-NF-κB, and caspase-3 (P < 0.01), reduced the Bax/Bcl-2 rate (P < 0.01), and decreased the concentrations of IL-1β (P < 0.01) and TNF-α (P < 0.05). Conclusion: LBP could improve both retinal morphology and function, providing protection to photoreceptors from apoptosis through the inhibition of the NF-κB/NLRP3 pathway.